GWAS shows links between EDARADD and LRFN5 and performance in professional athletes - Terekhov, M. V.; Deev, R. V.; Kadykova, A. I.; Dzhumaniiazova, I. H.; Mamchur, A. A.; Zelenova, E. A.; Matkava, L. R.; Ivanov, M. V.; Kashtanova, D. A.; Mitrofanov, S. I.; Golubnikova, L. A.; Nekrasova, A. I.; et al. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Research into genetic markers associated with sports performance and aerobic capacity has been gaining momentum. However, despite the discovery of numerous molecular and genetic markers, there is still a gap in understanding the variations in athletes` trainability and maximum oxygen consumption levels (VO2 max). The purpose of this study was to examine molecular and genetic markers associated with athletic performance and build linear models to evaluate the contributions of phenotype and genotype to VO2 max levels in professional athletes.